Photodynamic Therapy for Peri-Implant Diseases - Betul Rahman; Anirudh Balakrishna Acharya; Ruqaiyyah Siddiqui; Elise Verron; Zahi Badran (MDPI AG, 2022)
Peri-implant diseases are frequently presented in patients with dental implants. This category of inflammatory infections includes peri-implant mucositis and peri-implantitis that are primarily caused by the oral bacteria that colonize the implant and the supporting soft and hard tissues. Other factors also contribute to the pathogenesis of peri-implant diseases. Based on established microbial etiology, mechanical debridement has been the standard management approach for peri-implant diseases. To enhance the improvement of therapeutic outcomes, adjunctive treatment in the form of antibiotics, probiotics, lasers, etc. have been reported in the literature. Recently, the use of photodynamic therapy (PDT)/antimicrobial photodynamic therapy (aPDT) centered on the premise that a photoactive substance offers benefits in the resolution of peri-implant diseases has gained attention. Herein, the reported role of PDT in peri-implant diseases, as well as existing observations and opinions regarding PDT, are discussed.